Life after life [large type] : a novel - McCorkle, Jill, 1958- (Thorndike Press, 2013)
Award-winning author Jill McCorkle takes us on a splendid journey through time and memory. Constantly surprising, Life After Life is filled with a sense of wonder as the residents, staff, and neighbors of the Pine Haven retirement center share some of life's most profound discoveries. Some of the most true-to-life characters that you are ever likely to meet in fiction, what they learn about themselves and one another will transform them all. (Bestseller)